Kurikulum Pendidikan Agama Islam - Rahmayanti, Rahmayanti; Iswantir, Iswantir (Prodi Pendidikan Agama Islam IAINU Kebumen, 2024)
This paper aims to analyze the development of the Islamic education curriculum using a literature review method and comparative analysis, which involves examining various relevant books, journals, and documents, as well as comparing the differences and similarities between different curricula. The research findings indicate that the Islamic education curriculum in Indonesia has gone through four phases: the pre-independence period, the Old Order, the New Order, and the current reform era. In the pre-independence period, the curriculum was heavily influenced by colonialism. During the Old Order, three curricula were implemented: the 1947, 1984, and 1994 curricula. Meanwhile, during the New Order, the curriculum was divided into four, namely 1968, 1975, 1984, and 1994 curricula. Finally, the reform era up to the present includes four curricula: the 2004 curriculum (KBK), the 2006 curriculum (KTSP), the 2013 curriculum, and the independent curriculum.